2016
DOI: 10.3847/1538-4357/833/2/222
|View full text |Cite
|
Sign up to set email alerts
|

THE FINAL SDSS HIGH-REDSHIFT QUASAR SAMPLE OF 52 QUASARS AT z > 5.7

Abstract: We present the discovery of nine quasars at z ∼ 6 identified in the Sloan Digital Sky Survey (SDSS) imaging data. This completes our survey of z ∼ 6 quasars in the SDSS footprint. Our final sample consists of 52 quasars at 5.7 < z ≤ 6.4, including 29 quasars with z AB ≤ 20 mag selected from 11,240 deg 2 of the SDSS single-epoch imaging survey (the main survey), 10 quasars with 20 ≤ z AB ≤ 20.5 selected from 4223 deg 2 of the SDSS overlap regions (regions with two or more imaging scans), and 13 quasars down to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
421
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 323 publications
(458 citation statements)
references
References 119 publications
(171 reference statements)
32
421
5
Order By: Relevance
“…We see that the model shows good agreement with observations across a large redshift range (z ∼ 6 − 0.6). At high redshift the model is consistent with the samples of bright quasars (Willott et al 2010;Shen & Kelly 2012;McGreer et al 2013;Jiang et al 2016) while it predicts a lower number density of faint quasars compared to the Giallongo et al (2015, hereafter the G15) sample. On the other hand, the model produces a significant number of faint quasars.…”
Section: Quasar Luminosity Functionsupporting
confidence: 70%
“…We see that the model shows good agreement with observations across a large redshift range (z ∼ 6 − 0.6). At high redshift the model is consistent with the samples of bright quasars (Willott et al 2010;Shen & Kelly 2012;McGreer et al 2013;Jiang et al 2016) while it predicts a lower number density of faint quasars compared to the Giallongo et al (2015, hereafter the G15) sample. On the other hand, the model produces a significant number of faint quasars.…”
Section: Quasar Luminosity Functionsupporting
confidence: 70%
“…McGreer et al (2013) derived the quasar spatial density at z ∼ 4, 4.9, and 6, and fitted a luminosity-dependent density evolution model to the combined data set. They concluded that the quasar number density evolution steepens at high redshift, such that luminous quasars decline as a population more steeply at z > 5 than from z=4 to z=5 (also Jiang et al 2016). However, the exact evolution of quasar density from z=5 to 6 is unclear because of the small size and high incompleteness of the existing z ∼ 5.5 quasar sample.…”
Section: Introductionmentioning
confidence: 99%
“…Bright quasars have also been detected at similar cosmic epoch, when the Universe was younger than a billion years (Fan 2001;Fan et al 2006;Venemans et al 2013;Bañados et al 2016;Jiang et al 2016;Matsuoka et al 2016), while the population of fainter quasars is still small (Willott et al 2010;Matsuoka et al 2016). Currently, high-redshift galaxies and quasars are studied almost separately.…”
Section: Introductionmentioning
confidence: 99%